1989
DOI: 10.1111/j.1464-410x.1989.tb05525.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in the Surgical Treatment of Azoospermia

Abstract: Surgery for male obstructive infertility is not always successful. A number of clinical and operative findings, not previously reported, may influence the outcome. We have studied 182 patients with azoospermia who underwent vasoepididymostomy. The pre-operative and operative findings which adversely affected the function of the anastomosis were identified. The presence of spermatozoa in the semen sample was taken to mean a successful anastomosis. Abnormal testicular histology was an adverse pre-operative findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Antisperm antibodies did not preclude a favourable outcome and three of nine men who had antisperm antibodies achieved pregnancies after steroid therapy. Kapur et al [ 17] examined factors predictive of outcome in epididymovasostomy and concluded that abnormal testicular histology, epididymal hypoplasia and absence of epididymal fluid at exploration were independent negative predictors of success. However, Niederberger and Ross [ 18] suggested that the presence or absence of sperm in the epididymal fluid at the time of microsurgical epididymovasostomy was the most important single predictor of outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Antisperm antibodies did not preclude a favourable outcome and three of nine men who had antisperm antibodies achieved pregnancies after steroid therapy. Kapur et al [ 17] examined factors predictive of outcome in epididymovasostomy and concluded that abnormal testicular histology, epididymal hypoplasia and absence of epididymal fluid at exploration were independent negative predictors of success. However, Niederberger and Ross [ 18] suggested that the presence or absence of sperm in the epididymal fluid at the time of microsurgical epididymovasostomy was the most important single predictor of outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Kapur et al . [24] in 1989 reported their results of vasoepididymostomy and found a patency rate of 59% in the absence of adverse factors such as abnormal histology, absence of fluid in the epididymis or hypoplastic epididymis. We have recently reported our modifications and outcomes with both the standard two-suture and longitudinal two-suture techniques of VEA in men with idiopathic vaso-epididymal obstruction.…”
Section: Outcomes Reportingmentioning
confidence: 99%